Effects of multi-walled carbon nanotubes on char residue and carbothermal reduction reaction in ethylene propylene diene monomer composites at high temperature. (20th January 2020) - Guo, Mengfei; Li, Jiang; Xi, Kun; Liu, Yang; Ji, Jianbo; Ye, Changqing
Abstract: Mechanistic investigation of the effect of nanofillers on the ablation of composites is essential to meet the demand for high-performance ablative composites. Ethylene propylene diene monomer (EPDM) composites with and without 5 wt% multi-walled carbon nanotubes (MWCNTs) are prepared, and their ablation rates are tested using a solid rocket motor. The carbothermal reduction reaction during ablation is studied using a high-temperature tube furnace. The carbothermal reduction reaction of silica at high temperature results in a large consumption of char, and is an important reaction affecting the ablation process. The addition of MWCNTs increases the char residue of EPDM composites. MWCNTs can enhance the rate-limiting reaction, thereby reducing the released gas and increasing the production of SiC. The network structure of MWCNTs in char has a directional effect on the in-situ formation of SiCw, which can improve the ablation resistance of composite.